THE SKILL INTEGRATION IN TEACHING ENGLISH - Rakhmatullayeva Dilrabo (Journals Park Publishing, 2024)
The article is aimed to explain the importance of skills integration in teaching foreign languages and determines the structures of integrated approach. Furthermore, the research analyzes three main levels of skills integration in the lesson.
Keywords: Integration, method, skill, learner, teaching, communication, content-based, task-based.